Polaronic effects in electron shuttling - Skorobagatko, Gleb A.; Krive, Ilya V.; Shekhter, Robert I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
Shuttle-like mechanism of electron transport through a single level vibrating quantum dot is considered in the regime of strong electromechanical coupling. It is shown that the increment of shuttle instability is a nonmonotonic function of the driving voltage. The interplay of two oppositively acting effects—vibron-assisted electron tunneling and polaronic blockade — results in oscillations of the increment on the energy scale of vibron energy.